EFFICIENCY OF CORRECTIONAL WORK WITH VISUALLY IMPAIRED PRESCHOOL CHILDREN - Olena І. Perevorska; Abagyan E. (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The paper considers the problem of correctional work efficiency with visually impaired preschool children. The theoretical analysis of the problem showed that the insufficient level of communicative skills and speech development of visually impaired preschool children hinders comprehensive communication, causes difficulties in mastering the speech cycle material, hampers their successful learning. The education of such a child provides them with an opportunity of gaining experience of social behavior and join public life, gain confidence, freedom of thought, maximum possible independence. The authors emphasize that the solution to the problem will be the introduction of a correctional and developmental program aimed at communicative and speech development of visually impaired preschool children. We conducted a study of the level of communicative and speech development of visually impaired preschool children in three stages. The study involved 32 visually impaired preschool children, divided into two groups (experimental and control). The results of the study allowed us to conclude that targeted, systematic, consistent correctional and developmental work contributes to the communicative and speech development of visually impaired preschool children in the educational process. There are positive changes in the level of communicative skills and speech development of visually impaired preschool children. So, the obtained results prove the effectiveness of correctional work with them. R